Staged Management of Congenital Chylothorax With Hydrops Fetalis: An Insight Into EXIT Related Procedures - Tai, Hung-Lin; Mok, Tze Yee Diane; Chao, An-Shine; Chu, Shih-Ming; Lien, Reyin (Frontiers in Pediatrics, 2021)
Background: Idiopathic congenital chylothorax is a rare but serious disease. Advancement in perinatal care and the renovated treatment modalities have brought about significant improvement in patient outcome. Objective: To describe the clinical course of severe forms of idiopathic congenital chylothorax, focusing on the development of recent treatment modalities and their impacts. Design: A retrospective cohort by review of medical records in the NICU of a perinatal referral center in Taiwan. Study period was from January 2006 to June 2017. Neonates with the diagnosis of idiopathic congenital chylothorax with non-immune hydrops fetalis were enrolled. Clinical relevant including demographic data, perinatal interventions, postnatal course, and treatment outcome were described and analyzed. Results: Twenty-eight neonatal patients were included. The median gestational age at birth was 34 (range 27-36) weeks and median birth weight was 2369 (range 1430-3608) grams. Prenatal intervention was performed in 39.3% of the patients. Besides, 11 out of the 28 neonates developed tension pneumothorax in the first 24 hours and 4 (36.4%) of them died. Sepsis was documented in 2 patients (7.1%). Overall survival rate was 71.4%. There were 5 patients enrolled during the last 2 years of the study period. EXIT with intubation was performed in two and octreotide was given to four of these most recent neonates, and all of them survived. Conclusion: Recent advances in the management of these neonates, specifically EXIT with intubation and use of octreotide. Both of them improved patient survival in our cohort, but the evidence of impact has yet to be validated.